Unsettled Minds : Psychology and the American Search for Spiritual Assurance, 1830-1940 - White, Christopher G., 1969- (University of California Press, 2009)
'Unsettled Minds' examines how 19th- and 20th-century American beleivers rejected older, often evangelical theological traditions and turned to scientific psychologies to formulate new ideas about mind and spirit and new practices for spiritual growth.